Experimental Investigation of an Algorithmic Approach for Optimizing DAB Converter Design - Rossano Mendes Sotoriva; Mateus de Freitas Bueno; Douglas Mendes Sotoriva; Franciéli Lima de Sá; Samir Ahmad Mussa (Eletrônica de Potência)
This study endeavors to optimize a dual active bridge (DAB) converter for seamless integration into an electric vehicle's on-board charger (OBC). The optimization process employs an algorithm to ascertain the optimal construction parameters, encompassing factors such as the number of turns in the inductor, gap length, and the number of turns in the primary and secondary windings of the transformer. By considering seven meticulously chosen operating points, the objective is to minimize the total loss sum and pinpoint the optimal frequencies for each point. Subsequently, a lookup table is formulated to ensure efficient OBC operation across varying output power and current levels by optimizing the frequency as a single variable. To validate the optimization process, the power switch losses are compared with theoretical calculations, and simulation results from PLECS 4.7.2 are leveraged. Furthermore, a prototype is meticulously assembled and tested to validate the DAB converter optimization, ultimately achieving an impressive efficiency of over 97 %, thus affirming the efficacy of the optimization algorithm.